RELIGIOUS FUNCTIONAL STYLE OF MACEDONIAN LANGUAGE (Philological Studies, 2024)
The paperpaper contains an analysis of the religious functional style of Macedonian language, firstly with a review of the translation of the Old Testament and New Testament into Macedonian, namely the first edition in 1990 and the second revised edition in 2006. Several features are taken in regard: usage of verb and case forms, main lexical features and characteristics of word-formation, usage of synonymous and antonymous constructions, word order and cohesive elements. A significant role in the development of the religious functional style has been played by the periodicals published by the dioceses of the Macedonian Orthodox Church, as well as the web portals such as Премин (www.preminportal.com.mk), which are viewed within the framework of the publicistic and religious functional styles.Several novels from two Macedonian contemporary authors (Dragi Mihajlovski and Olivera Nikolova) were also considered as part of the religious functional stylistic complex of Macedonian. The analysis covers the usage of vocabulary, word-formation features linked to the Old Church Slavic and Biblical tradition, as well as usage of language borrowings, biblical phrases etc.The aim of this analysis is to establish the main characteristics of the religious functionalstylistic complex of Macedonian language, such as lexical and word-formation features, usage of archaic words and language borrowings (from Hebrew and Greek) and their adaptation, cohesive elements in the texts etc.